Association between magnesium intake and the risk of anemia among adults in the United States - Huang, Jungao; Xu, Jing; Ye, Ping; Xin, Xiaoqin (Frontiers in Nutrition, 2023)
Background: Magnesium deficiency is related to an increased risk of anemia, but epidemiological evidence supporting this association remains scarce. The purpose of the present survey was to evaluate the relationship between dietary magnesium intake and the risk of anemia. Methods: A total of 13423 participants aged 20 years and older were enrolled using the National Health and Nutrition Examination Survey (NHANES) 2011–2016. Magnesium consumption was obtained from 24 h dietary recalls. Multivariable generalized linear models were conducted to demonstrate the association between dietary magnesium intake and the prevalence of anemia. Results: An inverse association between dietary magnesium intake and the risk of anemia was detected based on a full adjustment model. We clarified magnesium intake as a categorical variable (five quartiles). Compared with the lowest value, the highest multivariate adjusted odds ratio (95% confidence interval) of anemia was 0.64 (0.46~0.89). In stratified analyses, we found a reverse relationship between magnesium intake and anemia for females. However, there was no statistical association for males (p for trend =0.376). A similar reverse association was evaluated among the older group (age≥60 years). Conclusions: Magnesium deficiency is closely related to a higher occurrence of anemia, especially among women and older Americans. Further larger-scale prospective studies are required to confirm these conclusions.